Javanese Ethnic Local Wisdom in Farmer Community Folklore in South Coastal Area of Kebumen, Central Java By MV Sri Hartini HS - Sri Hartini (Fakultas Bahasa dan Sastra Universitas Kanjuruhan Malang, 2017)
This research aimed to describe the Javanese ethnic local wisdom in farmer community folklore of South coastal area of Kebumen. The problems studied were how the existence of folklore was in farmer community folklore of South coastal area of Kebumen and what local wisdoms were implied in their folklore. The data analyzed was oral folklore consisting of four criteria, partially oral folklore constituting farming sector rite, and non-oral folklore constituting food, drugs, and traditional house. The approach method used was an ethnographic descriptive qualitative with ethnoscientific analysis model. The data was collected using in-depth interview with selected informant. The sample of research was the farmer community of South coastal area of Kebumen Regency. The result of research showed that folklore in farmer community contained local wisdoms: 1) local cultural, 2) local spiritual. 3) local educative, 4) local symbolic, 5) local economic, 6) local practical, and local historic. In addition to containing local wisdom, folklore also served as education to the next generation as preserving the wisdom inherent to farmer environment.